Evaluation of the different substrates for composting in the cultivation of Agaricus bisporus under the agro-ecological condition of West Bengal - C. Shanmugaraj; K. Saranraj; M.K. Biswas (Mushroom Research, 2025)
Mushrooms offer a nutrient-dense, low-fat dietary option while serving as an eco-friendly solution for repurposing agricultural waste through cultivation. The study focuses on cultivating Agaricus bisporus, or button mushrooms, in the lateritic belt of West Bengal, India, using the Long Method of Composting. Various substrates—paddy straw, maize stalks, and combinations thereof were evaluated. Results show that the 1:1 ratio of paddy straw and maize stalks yielded the best outcomes, with the shortest spawn run period (20.33 days), earliest pinhead formation (15.33 days), and highest sporophore production (92/8 kg compost bag). This substrate also led to the earliest first harvest (9.33 days), highest yield (1020.00 g/8 kg bag), and biological efficiency (12.75%). Conversely, maize stalk compost had the lowest yield (643.33 g/8 kg bag) and biological efficiency (8.04%), and was susceptible to Coprinus spp. infestation. Overall, Paddy straw + Maize stalk (1:1) compost proved superior, offering faster cultivation and higher yields, making it the optimal choice for A. bisporus cultivation.